2019
DOI: 10.1088/1757-899x/518/2/022088
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Consideration In Flood Mitigation And River Restoration

Abstract: One of the fundamental section of sustainable improvement in river basin systems and has multifunctional targets is river restoration. The targets of river restoration are to minimize the physical degradation and recover river elegance value, pollution manage and good ecosystem with biodiversity. River restoration is a multidisciplinary task in which engineer, hydrologist, geologist and ecologist can work together to enhance river environment. In decades ago, Malaysia was exposed to fast evolution and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…Similarly, restoration entails restoring a deteriorated river to its original state (Minakshi & Goswami, 2014). It also can be defined as actions taken to the rivers and their basins that have experienced critical pollution damage to their natural habitats to return the rivers to their original states before the damage (Saad et al, 2019). However, some researchers have asserted that river restoration may be impossible to achieve; thus, the work to treat the condition is commonly referred to as rehabilitation (Rutherfurd et al, 2000).…”
Section: River Rehabilitationmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, restoration entails restoring a deteriorated river to its original state (Minakshi & Goswami, 2014). It also can be defined as actions taken to the rivers and their basins that have experienced critical pollution damage to their natural habitats to return the rivers to their original states before the damage (Saad et al, 2019). However, some researchers have asserted that river restoration may be impossible to achieve; thus, the work to treat the condition is commonly referred to as rehabilitation (Rutherfurd et al, 2000).…”
Section: River Rehabilitationmentioning
confidence: 99%
“…Fig 2 illustrates the differences between the terms restoration, rehabilitation and remediation. Saad et al (2019) suggested that two approaches are primarily used to treat the river. The first approach is self-purification, in which the rivers will purify themselves through actions like flowing, dilution, deposition and absorption and recreating their natural course and flooding scheme (Saad et al, 2019).…”
Section: River Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Assim, o Quadro 1 destaca os aspectos que são atendidos totalmente (verde), parcialmente (amarelo), ou não são considerados (cinza) pelos termos citados. Sua construção foi possível a partir de buscas de cada terminologia na base de dados Scopus, sendo o termo "Restauração" o mais recorrente nos artigos mais recentes (MIGUEZ et al, 2015;PRIOR, 2016;BAPTISTA et al, 2017;MROZIŃSKA et al, 2018;BECKER;CHAPMAN;GO-MES;SAMMEN;SKRINAR et al, 2019;CHEN & CHO, 2019;PALMER & RUHI, 2019;BLAZY, 2019;ALENCAR & PORTO, 2019;WI-KANTIYOSO et al, 2020;). Percebe-se, a partir da análise dos artigos e do quadro resumo, que a proposta do termo Readequação tem o foco voltado para a funcionalidade, em termos antrópicos, dos rios e córregos urbanos, no sentido da promoção de serviços ecossistêmicos, aliado por sua vez a manutenção de uma qualidade ambiental satisfatória desses ecossistemas.…”
Section: Introductionunclassified